Usefulness of gram staining of blood collected from total parenteral nutrition catheter for rapid diagnosis of catheter-related sepsis. - Moonens, F (1994)
The accuracy of Gram staining of blood drawn from catheters used to administer total parenteral nutrition was compared with paired quantitative blood cultures for the diagnosis of catheter-related sepsis. Gram staining was positive in 11 of 18 episodes of catheter-related sepsis documented by quantitative culture (sensitivity, 61%) but in none of the 5 episodes of fever unrelated to catheter infection. Thus, this procedure enabled the rapid presumptive diagnosis and guidance of antimicrobial therapy for total parenteral nutrition catheter sepsis, with a positive predictive value of 100% and a negative predictive value of 42%.